2014
DOI: 10.1523/jneurosci.1348-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ Deficiency in Myeloid Cells Ameliorates Alzheimer's Disease-Related Symptoms and Pathology

Abstract: Alzheimer's disease (AD) is characterized by extracellular amyloid-␤ (A␤) deposits and microglia-dominated inflammatory activation.Innate immune signaling controls microglial inflammatory activities and A␤ clearance. However, studies examining innate immunity in A␤ pathology and neuronal degeneration have produced conflicting results. In this study, we investigated the pathogenic role of innate immunity in AD by ablating a key signaling molecule, IKK␤, specifically in the myeloid cells of TgCRND8 APP-transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 71 publications
4
60
1
Order By: Relevance
“…All images were acquired by Zeiss AxioImager.Z2 microscope equipped with a Stereo Investigator system (MBF Bioscience, Williston). In the whole hippocampus and cortex, volumes of A␤ and brain tissues were estimated with the Cavalieri probe as we described in the previous study (30) with a 15-m grid size, which provided coefficient of error estimates of Ͻ0.05. The A␤ load was demonstrated as the ratio of A␤ volume to relevant brain tissue volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All images were acquired by Zeiss AxioImager.Z2 microscope equipped with a Stereo Investigator system (MBF Bioscience, Williston). In the whole hippocampus and cortex, volumes of A␤ and brain tissues were estimated with the Cavalieri probe as we described in the previous study (30) with a 15-m grid size, which provided coefficient of error estimates of Ͻ0.05. The A␤ load was demonstrated as the ratio of A␤ volume to relevant brain tissue volume.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the histological analysis using the stereological Cavalieri method (30) revealed that heterozygous deletion of p38␣ MAPK in neurons resulted in strongly reduced A␤ levels in both the hippocampus and cortex of APP-transgenic mice, even as early as 4 months of age (APP tg p38 fl/wt Nex-Cre fl/fl Nex-Cre Ϫ/Ϫ , but without the expression of human APP. We observed that neuronal p38␣ MAPK deletion significantly reduced the activity of ␤-secretase, but not of ␥-secretase, in a copy-dependent manner (Fig.…”
Section: Deletion Of P38␣ Mapk In Neurons Reduces A␤ Load In the Alzhmentioning
confidence: 99%
“…C57BL/6J mice were originally imported from Charles River Laboratories and bred in our animal facilities. To establish mice with modified inflammatory activation specifically in myeloid cells, we cross-bred ikbkb fl/fl (24), MyD88 fl/fl (25), or p38a fl/fl (26) mice with LysM-Cre knock-in mice expressing Cre from the endogenous lysozyme 2 gene locus (27) as we did previously (9) LysM-Cre +/2 mice, respectively, and their effects on inflammatory responses in mice have been previously described (28)(29)(30). To estimate the efficiency of LysMCre-mediated gene recombination of floxed ikbkb, myd88, and p38a-mapk genes in myeloid cells, we cross-bred LysM-Cre mice to ROSA mT/mG Cre reporter mice (The Jackson Laboratory, stock no.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Aggregated Ab activates microglia through CD14/TLR2/TLR4-MyD88-kinase of NF-kB inhibitor (IKK) b signaling pathway (6)(7)(8)(9)(10). In p-Tau-induced AD pathogenesis, inflammatory activation might serve as a two-edged sword: on one side, certain inflammatory cytokines, such as IL-1b, promote phosphorylation and aggregation of Tau by activating p38a-MAPK in neurons (11)(12)(13).…”
mentioning
confidence: 99%
“…It is well established that NF-B and STAT3 are transcription factors that participate in cytokine and growth factor actions in immune cells and transcription of a variety of genes involved in inflammation, cellular adaptation to stress, and cell death (36). Activated IKK␤ phosphorylates IB and triggers its degradation by proteasomes, and this process results in translocation of NF-B to the nucleus and the induction of NF-B-dependent transcription of a wide range of immune and inflammatory genes (37). Recently, research has found that the NF-B signal pathway is central to many macrophage (25) and microglial functions, including phagocytosis and cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%